(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
In the contemporary context of globalisation, the literal and superficial interpretation of theological terms found in Quranic verses and hadiths has become increasingly prevalent, generating doctrinal confusion particularly around the question of whether God possesses physical attributes. This article examines pseudo-Salafi claims concerning the concept of “istawa” – God’s “settling upon the Throne” – and presents comprehensive textual (naqliy) and rational (aqliy) refutations drawn from the Hanafi- Maturidi theological tradition. The study analyzes the Quranic distinction between clear (muhkam) and ambiguous (mutashabih) verses, examines the distorted use of classical sources by Ibn Taymiyya and Muhammad ibn Abd al-Wahhab, and presents authentic transmissions from Imam Malik and the early pious predecessors (salaf al-salih). The findings affirm that the mainstream Ahl al-Sunna wa al-Jama‘a position – that God exists without place, direction, or bodily attributec – is firmly grounded in Quranic exegesis, sound hadith, and incontrovertible rational argument.